2014
DOI: 10.1007/s00428-014-1674-7
|View full text |Cite
|
Sign up to set email alerts
|

NRAS-mutated melanocytic BAP1-associated intradermal tumor (MBAIT): a case report

Abstract: Melanocytic BAP1-associated intradermal tumors (MBAITs) are epithelioid spitzoid looking, mostly intradermally located melanocytic tumors that often have tumor-infiltrating lymphocytes and a common nevus component. They occur sporadically but also in the context of an underlying BAP1 germline mutation. Recognition of these lesions is important because they can be a marker for an underlying BAP1-associated cancer syndrome. Most cases reported in the literature thus far were found to have both a BRAF and BAP1 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…This model of progression of BIMT from a benign nevus was proposed in the original description 8 and is also supported from a molecular viewpoint, inasmuch as both combined and pure cases in our series and in the previously reported ones 2,5,33 harbored a BRAF V600E mutation in the presence of BAP1 inactivation. Moreover, combined type BIMTs have also been reported in association with an NRAS mutation and RAF1 fusions 3,4,33 , both known to act as a mitogenic driver in melanocytic neoplasms 34 . Fusions involving receptor tyrosine kinases and serine/threonine kinases Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model of progression of BIMT from a benign nevus was proposed in the original description 8 and is also supported from a molecular viewpoint, inasmuch as both combined and pure cases in our series and in the previously reported ones 2,5,33 harbored a BRAF V600E mutation in the presence of BAP1 inactivation. Moreover, combined type BIMTs have also been reported in association with an NRAS mutation and RAF1 fusions 3,4,33 , both known to act as a mitogenic driver in melanocytic neoplasms 34 . Fusions involving receptor tyrosine kinases and serine/threonine kinases Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for such an interpretation is the identification of remnants of a conventional nevus with retained nuclear expression of BAP1 in many cases of BIMT that is otherwise mainly composed of BAP1-negative large epithelioid melanocytes with well-demarcated cytoplasmic borders and copious eosinophilic cytoplasm. From a molecular biological viewpoint, it is characterized by a BRAF mutation (or, rarely, NRAS mutation or RAF1 fusion) considered to represent a mitogenic driver alteration and biallelic inactivation of the BAP1 gene, leading to dysfunction of BAP1 protein [2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Two had BRAF V600E mutations while one had an NRAS mutation. Prior studies have shown that BIMTs are commonly associated with BRAF V600E mutations, but only rare cases have shown NRAS mutations 3,6,7,26–30 . As such, we were unable to identify driver mutations in two cases, but this is likely because of the limited panel of genes in the assay.…”
Section: Discussionmentioning
confidence: 82%
“…Prior studies have shown that BIMTs are commonly associated with BRAF V600E mutations, but only rare cases have shown NRAS mutations. 3,6,7,[26][27][28][29][30] As such, we were unable to identify driver mutations in two cases, but this is likely because of the limited panel of genes in the assay. While criteria such as cytologic atypia, lack of maturity, and positive staining for one or more of the melanoma markers aided in the initial diagnosis of melanoma for these cases, there may be instances in which BIMTs do not present with all of these characteristics to be called a melanoma on morphology or immunohistochemical staining alone.…”
Section: Discussionmentioning
confidence: 96%
“…While not very common, some cases of Wiesner nevus without BRAF mutation have been reported (around 10% of cases), first in the initial description of the genetic syndrome and later in reports of sporadic cases . The current report of BAP1‐negative and VE1‐negative AST should help to define AST with loss of BAP1 expression further.…”
Section: Discussionmentioning
confidence: 99%